Media Visual untuk Meningkatkan Prestasi Belajar pada Pembelajaran IPS di Kelas VI SDN Bahoea Reko-Reko - Ilarmin, Ilarmin; Amus, Sunarto; Misnah, Misnah; Juraid, Juraid; Ratu, Bau; Elfira, Ninil (Universitas Batanghari Jambi, 2024)
Social studies is known as boring and lazy learning because there are history lessons whose form cannot be seen directly. Therefore, visual learning media is needed which is assumed to be able to help teachers in social studies learning. This research was conducted to analyze the use of visual media in social studies learning. This research uses library methods to collect data and information related to identifying articles, books and supporting documents which are then analyzed. The research results show that utilizing visual media can help students develop visual abilities. Besides that, visual media is a learning tool that can develop students' imagination in learning activities. Thus, this research illustrates the use of visual media as a learning medium that can help students improve their mastery of events that are impossible to present in the classroom, such as social studies learning.